Sinetron Indonesia Menuju Perkembangan Sebagai Sarana Media Massa - Bunyamin Bunyamin Bunyamin (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2018)
Soap ope ras, better known as electronic cinema or teledrama, play a major role in society in understanding this real or real life and plugging in frames / images of thought in the future. In preparing for a global era and an increasingly advanced industrial society and intense competition in the global market, Indonesian soap operas must be able to play its role. Along with the increasing number of private TV sets, quantitatively Indonesian soap operas experienced a very proud development and also gave a variety of nuances, however the quality of Indonesian soap operas has only recently developed. Indonesian soap operas must consider the elements of education, entertainment, the real problems of society and the way they are done, such as the DKI reborn Warkop film which has a classic feel but is still interesting as a television broadcast that is comedy and educating. Actually, if we want to emulate a very educational cartoon film such as Upin and Ipin, Shiva even though the results of neighboring state products contain a message of education and a very high moral message, Indonesian children love cartoon films like this, besides being funny, educating , raising local culture, and introducing the name of a particular place. Indonesian television shows are still dominated by shows that are beyond human reach. How much television is still mystical like in the Antv program, almost every day cannot be separated from mystical shows (Eyes of the Dark, Penetrating the inner eye, GGS and others).